Answer :

(i) Given that,

x - = 3


Squaring both sides, we get


(x - )2 = (3)2


x2 - 2 × x × + ()2 = 9


x2 - 2 + = 9


x2 + = 11


(ii) Squaring both sides, we get


(x2 + )2 = (11)2


(x2)2 + 2 × x2 × + ()2 = 121


x4 + 2 + = 121


x4 + = 119


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

What must be addeRD Sharma - Mathematics

Fill in the blankNCERT - Mathematics Exemplar

Show that:
</p
RD Sharma - Mathematics